Effect of Central Bank of Nigeria Daily Cash Withdrawal Policy on Small and Medium Enterprises in FCT, Nigeria - Ngbede, Adeyi; Itodo , Sylvanus Mohammed; James, Kwaghza Aondoaver (Kashere Journal of Politics and International Relations, 2025)
The study examines the effects of the central bank of Nigeria daily cash withdrawal policy on Small and Medium Enterprises (SMEs) in Nigeria's Federal Capital Territory (FCT) and analyzes their adaptation strategies. Following the Central Bank of Nigeria's implementation of cash withdrawal limits in December 2022, SMEs have faced significant operational challenges in transitioning from cash-based transactions to digital payment systems. Using a descriptive survey research design, the study collected data from 357 SMEs selected through simple random sampling from a population of 4,829 registered SMEs in FCT. Data was gathered using a structured questionnaire based on a four-point Likert scale, and analysis was conducted using mean scores and standard deviations. The findings reveal that the policy has significantly impacted SME operations, with increased operational costs emerging as the most significant effect (mean=3.68, SD=0.76). Customer transactions showed substantial reduction (mean=3.55, SD=0.89), and transaction efficiency was notably affected (mean=3.42, SD=0.82). In response, SMEs have implemented various adaptation strategies, with digital payment solutions showing the highest adoption rate (mean=3.75, SD=0.68), followed by investment in POS and electronic payment systems (mean=3.58, SD=0.77). The study concludes that while the cash withdrawal policy has created operational challenges for SMEs, it has also accelerated their adoption of digital payment solutions. The research recommends implementing a tiered cash withdrawal limit system and developing targeted support programs to assist SMEs in their digital transformation process.